Industrial safety in metallurgical company - T. Karkoszka (Metalurgija, 2023)
Steel mills, due to the used chemical substances of combustible, toxic and explosive properties as well as because of the many other threats to the environment, human and property – must ensure the industrial safety. Therefore, it should cover actions minimising the occurrence probability and limiting the importance of threats and their effects. In the study, one has presented the scheme of solutions within the range of safe realisation of the processes and loss prevention, concerning both: technical aspects of used technological and measurement control devices as well as the organisational aspects of processes realisation. For the chosen threats one has proposed actions for prevention, protection and limitation realised as technological and organisational layers of protection, which can be applied in the regular conditions as well as during dangerous event.